Violation of the Code of Ethics of the Accountant Profession at PT Tiga Pilar of Prosperity Food Tbk - Kirani Salsabila; Sri Trisnaningsih (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to study the accounting profession and its role and analyze the code of ethics of public accountants by taking one of the cases of violation of the code of ethics of public accountants who conducted an audit at PT Tiga Pilar Sejahtera Food Tbk. Based on the results of the analysis of the case, KAP Ernt and Young found that there was an overstatement of receivables and income and the flow of funds was not disclosed to affiliated parties. As a result of this violation, the two former directors, Joko Mogoginto and Budhi Istanto, who were suspected of being involved in this case, were sentenced to 4 years in prison and each fined Rp 2 billion. This ethical violation has serious negative consequences for the integrity of financial statements and public trust.